PEMODELAN UML SISTEM INFORMASI PERPUSTAKAAN PADA USN PAPUA - Nadia Nadia; Ghina Tripasha, Fheisyach Artianshal Karubun, Dwi andiyani, Grace Adelin Rumbairusy, grisye f silaho (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Libraries are an important component in supporting the teaching and learning process in educational institutions, including at the University of Science and Technology (USN) Papua. To improve the efficiency of data management and information services, a structured and easily developed web-based library information system is needed. This study aims to design a library information system using the Unified Modelling Language (UML) approach as a modelling tool. The diagrams used include activity diagrams and class diagrams to illustrate business processes such as book data management, member management, borrowing, returning, and reporting. The modelling results show a systematic workflow and the interrelationships between entities in the system. With this modelling, it is hoped that the development of a library information system at USN Papua can be carried out more effectively and support digital transformation in academic services